Umbilical Artery Lactate Correlates with Brain Lactate in Term Infants - Cahill, Alison G.; Macones, George A.; Smyser, Christopher D.; López, Julia D.; Inder, Terrie E.; Mathur, Amit M. (American Journal of Perinatology, 2017)
Objective The objective of this study was to determine the correlation between umbilical artery lactate with brain lactate in nonanomalous term infants.Study Design We performed a nested case–control study within an on-going prospective cohort of more than 8,000 consecutive singleton term (≥ 37 weeks) nonanomalous infants. Neonates underwent cerebral magnetic resonance imaging (MRI) within the first 72 hours of life. Cases (umbilical artery pH ≤ 7.10) were gender and race matched 1:3 to controls (umbilical artery pH > 7.20). Single voxel magnetic resonance spectroscopy (MRS), lactate, and N-acetyl aspartate (NAA) for normalization were calculated using Siemens software (Plano, TX). Linear regression estimated the association between incremental change in umbilical artery lactate and brain lactate, both directly and as a ratio with NAA.Results Of 175 infants who underwent MRI with spectral sequencing, 52 infants had detectable brain lactate. The 52 infants with brain lactate peaks had umbilical artery lactate values of 1.6 to 11.4 mmol/L. For every 1.0 mmol/L increase in umbilical artery lactate, there was an increase in brain lactate of 0.02, which remained significant even when corrected for NAA.Conclusion MRS measured brain lactate is significantly correlated with umbilical artery lactate in nonanomalous term infants, which may help explain the observed association between umbilical artery lactate and neurologic morbidity.
Keywords: cerebral lactate; umbilical artery lactate; brain injury; magnetic resonance spectroscopy